Obesity Prevention Interventions and Implications for Energy Balance in the United States and Mexico: A Systematic Review of the Evidence and Meta‐Analysis. Issue 9 (20th July 2019) - Richardson, Andrea S.; Chen, Christine; Sturm, Roland; Azhar, Gulrez; Miles, Jeremy; Larkin, Jody; Motala, Aneesa; Hempel, Susanne
Abstract : Objective: Obesity is preventable and yet continues to be a major risk factor for chronic disease. Multiple prevention approaches have been proposed across multiple settings where people live, work, learn, worship, and play. This review searched the vast literature on obesity prevention interventions to assess their effects on daily energy consumed and energy expended. Methods: This systematic review (PROSPERO registration CRD42017077083) searched seven databases for systematic reviews and studies reporting energy intake and expenditure. Two independent reviewers screened 5, 977 citations; data abstraction supported an evidence map, comprehensive evidence tables, and meta‐analysis; critical appraisal assessed risk of bias; and the quality of evidence was evaluated using Grading of Recommendations Assessment, Development and Evaluation (GRADE). Results: Hundreds of published reviews were identified. However, few studies reported on energy intake and expenditure to determine intervention success. Ninety‐nine studies across all intervention domains were identified. Few areas demonstrated statistically significant effects across studies; school‐based approaches and health care initiatives reduced energy consumed, education reduced energy consumed and increased energy expended, and social‐group approaches increased energy expenditure. Conclusions: Despite the amount of research on obesity prevention interventions, very few studies have provided relevant information on energy intake and expenditure, two factors determining weight gain. Future research needs to fill this gap to identify successful public health policies.